Osadnictwo ma wyspie Thira (Santoryn) od neolitu po późną epokę brązu - Kufel, Mariusz (Folia Praehistorica Posnaniensia, 2018)
This article presents a history of the Thera Island occupation in the Neolithic and Bronze Age. Altogether, 13 settlements and 2 cemeteries have been recorded from this period. The island was inhabited until the Late Bronze Age. The most significant centre on the island was surely the town of Akrotiri. At the beginning of the Late Bronze Age, a large eruption of the Santorini volcano took place which ceased the occupation and covered the almost entire island with a thick layer of pumice.